PURCHASING DECISIONS IN TERMS OF DIGITAL-BASED LIFESTYLE AND BRAND IMAGE - Marotina, R. Nia (UI Scholars Hub, 2025)
As the digital trend develops, people's lifestyles slowly change, tending to like something that is fast, easy, and practical that can be done via a smartphone. The purpose of this study was to determine whether a digital-based lifestyle affects purchasing decisions in the shopee marketplace, and to determine whether brand image affects purchasing decisions in the shopee marketplace in an Islamic economic perspective. This research is quantitative research. The research was conducted in Pekalongan Regency, the population in this study was Gen Z in Pekalongan Regency, the sample used in this study was 97 people. The technique used to analyze the data using Multiple Linear Regression Analysis with the help of SPSS 26 software. The results showed that in partial tests the Lifestyle variable had a positive and significant effect on Purchasing Decisions at Shopee. Lifestyle variables have a positive and significant effect on Purchasing Decisions at Marketplace Shopee, and in the simultaneous test the Lifestyle variable and the Brand Image variable together have a positive and significant effect on Purchasing Decisions at Marketplace Shopee. In the Coefficient of Determination test, the Adjusted R Square value is 0.791 (79.1%) and the remaining 20.9% is influenced by other variables not examined in this study.